A Systematic Review Compression Failure In Cold-Formed Steel (Cfs) Column Sections - Tarmizi, Nur Farah Izzati Mohd (Universiti Sains Malaysia, 2022)
This study presents the review on the compression failure of cold-formed steel (CFS) column sections and the method of conducting the study either experimentally or numerically. Compression failure is when the material itself yields or is crushed during a compression failure, not the entire column. When the axially loaded stress exceeds the allowed stress, shorter and broader columns typically fail under compression failure. An accurate prediction of the buckling behaviour and factors that are impacting the compression failure of CFS column sections was necessary due to the recent expansion of the use of CFS in industries and mid-rise structures. Although there were several research on buckling performance, they were not explicitly and properly explained. This research's goal is to give a systematic review of the literature on the compression failure of cold-formed steel (CFS) column sections. It also discusses possible study methods, such as experimental or numerical methods. In this review work, the compression failure of CFS column sections will be reviewed. From the studies, the factors that influenced the compression failure in CFS column sections have been discussed from the design parameter such as section properties, section geometry and additional materials. Then, several types and modes of compression failure have been discovered such as local, global and distortional buckling from the thirty-three research articles that have been reviewed.